2020
DOI: 10.3390/diagnostics11010029
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Association between Temporomandibular Disorders and Articular Eminence Inclination? A Systematic Review

Abstract: (1) Background: In order to determine the correlation between the inclination of articular eminence (AEI) and the development of temporomandibular disorders (TMDs), a systematic review was performed. (2) Methods: A systematic literature research was conducted between 1946 and January 2020, based on the following electronic databases: PubMed, Cochrane Library, Embase, Medline, Scope, SciELO, and Lilacs. Observational studies, analytical case-control studies, and cohort studies written in English were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…This may lead the mandible to move more vertically during the functional movement [6]. It is reported that a patient with steeper articular eminence is more likely to develop internal dysfunctions, such as anterior disk displacements, than a patient with a flatter articular eminence [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This may lead the mandible to move more vertically during the functional movement [6]. It is reported that a patient with steeper articular eminence is more likely to develop internal dysfunctions, such as anterior disk displacements, than a patient with a flatter articular eminence [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, not all patients with dislocation possess a steep AE slope. There have been many studies on the treatment of dislocation [7,8,10] or the relationship between the morphology of AE and disc displacement [11][12][13][14][15][16][17][18][19][20], but almost no studies have been found on the relationship between the morphology of AE and dislocation except for the study of Cohen et al [21]. In their study [21], the morphology of AE did not affect the anterior dislocation of the TMJ.…”
Section: Introductionmentioning
confidence: 99%
“…Two slopes have been described for the AE: the anterior slope (the non-articular slope) and the posterior slope (the articular slope, also known as the articular surface), the latter being covered by fibrocartilage. Of uttermost importance is the fact that the condylar process slides forward and downward along the posterior slope of the AE as the mandible moves anteriorly (7,13,14). The inclination of the path traversed by the condyle in relation to the AE during a protrusive or a contralateral mandibular movement is known as the condylar path/condylar guidance (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of function, the TMJ allows maximal free motion (it is a diarthrosis) ( 2 , 6 ), but also permits both hinging and gliding movements of the mandible within the three planes of space ( 7 ). Therefore, as the TMJ is considered a bicondylar diarthrosis, the two articular surfaces are represented by the condyle of the mandible and the bony eminence on the temporal bone (the articular tubercle or the articular eminence (AE) of the temporal bone) ( 2 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation